Measuring food policy research capacity: Indicators and Typologies - Babu, Suresh Chandra; Dorosh, Paul A. (International Food Policy Research Institute, 2013)
We surveyed 30 countries to measure the capacity of their individuals, organizations, and policy process system to undertake food and agricultural policy research. Our Food Policy Research Capacity Index, constructed using measures of human capacity (PhD full-time equivalent researchers per million rural residents), human capacity productivity (publications per PhD full-time equivalent researcher), and strength of institutions (the government effectiveness pillar of the Worldwide Governance Indicators), showed substantial variation across countries, with the Republic of South Africa, Colombia, and Ghana scored far higher than countries with similarly sized rural populations such as Liberia, Laos, Burundi, and Afghanistan.